South African Politics and Online Electioneering Discourses in Selected Social Media Sites in Phuthaditjhaba - Sinyonde, Bright (African Journal of Inter/Multidisciplinary Studies, 2024)
This study analyses electioneering discourses in selected social media sites of Phuthaditjhaba in South Africa. It focuses on political messages and images posted by political parties on selected Facebook Pages and X handles in Phuthaditjhaba. Using critical discourse analysis as a method and netnography as an instrument to collect data from selected sites, I analyse the packaging and language of political communication and highlighting socio-economic issues used by political parties to persuade voters and undermine messages of their competitors. The theoretical underpinnings of the study are drawn from Kubin and von Sikorski’s (2021) notions of ideological and affective polarisation, and Entman’s (1995) idea of social media constructions of poverty. Their ideas guide my analysis of how political rivals capitalise on existing socio-economic issues in Phuthaditjhaba to mobilise sentiment among disgruntled residents. Data was collected from ten social media sites namely, four Facebook group pages, four X group handles and two individual X handles. Ten images and accompanying texts were sampled from the selected sites. Thematic analysis was used to categorise the data. The findings of the study show that while politicians used social media for campaign purposes, residents of Phuthaditjhaba used it to contest, and challenge messages of political parties.